The Effect of a Mixture of Gasoline and Ethanol in a Direct Injection System Engine on Power and Specific Fuel Consumption - Fina Rizqiani; Irawan , Bambang (PT. ELSHAD TECHNOLOGY INDONESIA, 2024)
The use of fossil fuels as the main fuel for vehicles is one of the problems in the automotive industry, considering that supplies are increasingly running low. The use of renewable fuel is an alternative in dealing with this problem, one of which is the use of ethanol as a gasoline fuel mixture. Ethanol which can be obtained from plants is more promising in terms of energy sustainability, and the high octane value of ethanol allows for increased combustion efficiency and can produce optimal engine power. This research identifies the influence of gasoline-ethanol mixture and engine speed on power and specific fuel consumption in direct injection engines. The research was carried out by testing the power of an electric generator driven by a 1-cylinder direct injection engine, as well as calculating fuel consumption while the engine was operating. The results of this research show that the E10 produces the best performance at low and medium revs with the highest power of 0.119 kW and 0.490 kW, while the E5 is superior at high revs with a power of 0.644 kW. In terms of fuel efficiency, E15 has the lowest SFC at low speed (3.83 L/kWh), E10 at medium speed (0.96 L/kWh), and E5 at high speed (0.77 L/kWh). E20 shows the lowest efficiency in all runs. The results of this research can be used to design direct injection engines with mixed fuels consisting of gasoline, ethanol and diesel